Pelatihan Penulisan Karya Tulis (KTI) Bagi Guru-guru SMK di Kabupaten Jombang - Dwijayanti, Renny; Marlena, Novi; Patrikha, Finisica Dwijayati (Jurnal Pemberdayaan Masyarakat Madani (JPMM), 2017)
Professional teachers not only perform functions related to pedagogical competence, but also professional functions. Indicated by improve professional functions in writing scientific papers. This Community Service collaborates with two partners, which are teachers who are member of MGMP Office Administration and teachers in SMKN 1 Jombang. The aim of this Community Service is to train teachers to write scientific papers well, and publish their papers as well. These activities conducted in training activity, lecturing, question and answer, discuss and practice how to write scientific papers well. The result of these activities are 1) the implementation of this scientific writing training for vocational high school teachers is consistent to the steps that planned before, with two partners, which are teachers who are member of MGMP Office Administration and teachers in SMKN 1 Jombang, 2) the overall response from the participants of this scientific writing trainingare very satisfied, mainly because of the aspects of activities, speakers aspects, and general aspects.